Peptide-based inhibitors hold great promise as the broad-spectrum agents against coronavirus - Tang, Mingxing; Zhang, Xin; Huang, Yanhong; Cheng, Wenxiang; Qu, Jing; Gui, Shuiqing; Li, Liang; Li, Shuo (Frontiers in Microbiology, 2023)
SARS-CoV, MERS and the recent SARS-CoV-2 are lethal coronaviruses (CoVs) that have caused dreadful epidemic in a large region or globally. Infections of human respiratory systems and other important organs by these pathogenic viruses often results in high rates of morbidity and mortality. Efficient anti-viral drugs that can are still needed. Herein, we firstly take SARS-CoV-2 as an example to present the molecular mechanism of CoV infection cycle, including the receptor binding, viral entry, intracellular replication, virion assembly and release. Then according to their mode of action, we provide a summary of anti-viral peptides that have been reported in peer-reviewed publications. Even though CoVs can rapidly evolve to gain resistance to the conventional small molecule drugs, peptide-based inhibitors targeting various steps of CoV lifecycle remains a promising approach. Peptides can be continuously modified to improve their antiviral efficacy and spectrum along with the emergence of new viral variants.